An obituary to Professor A K M Rafiquddin : Words cannot express our grief (Bangladesh Medical Journal, 2014)
Abstract not available DOI: http://dx.doi.org/10.3329/bmj.v43i1.21383 Bangladesh Med J. 2014 January; 43 (1): 58-60